Risk of Immune-related Adverse Events in Melanoma Patients With Preexisting Autoimmune Disease Treated With Immune Checkpoint Inhibitors: A Population-based Study Using SEER-Medicare Data. (August 2021) - Tully, Karl H.; Cone, Eugene B.; Cole, Alexander P.; Sun, Maxine; Chen, Xi; Marchese, Maya; Roghmann, Florian; Kilbridge, Kerry L.; Trinh, Quoc-Dien
Abstract : Objective: The objective of this study was to examine the risk of immune-related adverse events (irAEs) in patients with a preexisting autoimmune disease (pAID) presenting with a cutaneous melanoma receiving an immune checkpoint inhibitor (ICI) therapy. Methods: Data from the Surveillance, Epidemiology, and End Results cancer registries and linked Medicare claims between January 2010 and December 2015 was used to identify patients diagnosed with cutaneous melanoma who had pAID or received ICI or both. Patients were then stratified into 3 groups: ICI+pAID, non-ICI+pAID, and ICI+non-pAID. Inverse probability of treatment weighted Cox proportional hazards regression models were fitted to assess the risk of cardiac, pulmonary, endocrine, and neurological irAE. Results: In total, 3704 individuals were included in the analysis. The majority of patients consisted of non-ICI+pAID patients (N=2706/73.1%), while 106 (2.9%) patients and 892 (24.1%) were classified as ICI+pAID and ICI+non-pAID, respectively. The risk of irAE was higher in the ICI+pAID group compared with the non-ICI+pAID and ICI+non-pAID, respectively (non-ICI: cardiac: hazard ratio [HR]=3.59, 95% confidence interval [CI]: 2.83-4.55; pulmonary: HR=3.94, 95% CI: 3.23-4.81; endocrine: HR=1.72, 95% CI: 1.53-1.93; neurological: HR=3.88, 95% CI: 2.30-6.57/non-pAID: cardiac: HR=3.83, 95% CI: 3.39-4.32; pulmonary: HR=2.08, 95% CI: 1.87-2.32; endocrine: HR=1.23, 95% CI: 1.14-1.32; neurological: HR=3.77, 95% CI: 2.75-5.18). Conclusions: Patients with a pAID face a significantly higher risk of irAEs. Further research examining the clinical impact of these events on the patients' oncological outcome and quality of life is urgently needed given our findings of significantly worse rates of adverse events. Abstract : Supplemental Digital Content is available in the text.